Influencia del taller "SPEAKING ENGLISH EASILY" en la producción oral del idioma inglés en los estudiantes de tercer grado "A" de secundaria de la Institución Educativa Nº0004 Túpac Amaru 2012 - Trujillo Coral, Cinthya Janeth (2012)
The following research report named "SPEAKING ENGLISH EASIL Y" in the English Language Oral Production for the students of third grade section "A" in Tupac Amaru Secondary School. Sorne objectives were proposed to develop this project, to test the "SPEAKING ENGLISH EASILY" workshop to improve English language learning. In order to achieve this objective, the research hypothesis (Hi) is that the "SPEAKING ENGLISH EASIL Y" workshop has significant influence on English language learning of students of the third grade "A" and "B" of Tupac Amaru secondary school. In order to test the hypothesis, a type of applied experimental level research was developed. The sample consisted of 23 students in the third grade of secondary school who resolved an evaluation before and after the application of the "SPEAKING ENGLISH EASIL Y" workshop. The pre and post-test data analysis of the experimental group has shown the average of the scores of pre and post-test is 4 and 19. The analysis and interpretation of experimental results of the "SPEAKING ENGLISH EASILY" workshop has significantly influenced the English language learning of students in third grade "A" of Tupac Amaru secondary school.